2014
DOI: 10.1002/jnr.23462
|View full text |Cite
|
Sign up to set email alerts
|

Glycans of myelin proteins

Abstract: Human P0 is the main myelin glycoprotein of the peripheral nervous system. It can bind six different glycans, all linked to Asn(93) , the unique glycosylation site. Other myelin glycoproteins, also with a single glycosylation site (PMP22 at Asn(36) , MOG at Asn(31) ), bind only one glycan. The MAG has 10 glycosylation sites; the glycoprotein OMgp has 11 glycosylation sites. Aside from P0, no comprehensive data are available on other myelin glycoproteins. Here we review and analyze all published data on the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 146 publications
(146 reference statements)
1
8
0
Order By: Relevance
“…8). The other glycans are not expected to interfere with dimerization, also not when considering myelin-specific N-linked glycans37. We confirmed that MAG dimerizes in solution via the Ig4–Ig5 interface by analysing glycosylated and deglycosylated forms of MAG 1–5 , MAG 1–3 (that lacks the dimerization domains) and the aforementioned mutants in small angle X-ray scattering (SAXS) and AUC experiments.…”
Section: Resultssupporting
confidence: 64%
“…8). The other glycans are not expected to interfere with dimerization, also not when considering myelin-specific N-linked glycans37. We confirmed that MAG dimerizes in solution via the Ig4–Ig5 interface by analysing glycosylated and deglycosylated forms of MAG 1–5 , MAG 1–3 (that lacks the dimerization domains) and the aforementioned mutants in small angle X-ray scattering (SAXS) and AUC experiments.…”
Section: Resultssupporting
confidence: 64%
“…Since no alterations are observed in the content of the abundant glycoprotein Mag (Figure ), which is highly sialylated (Sedzik, Jastrzebski, & Grandis, ), we studied the most sialylated species of gangliosides in the nervous system (Gong et al, ; Lunn et al, ; Vajn, Viljetic, Degmecic, Schnaar, & Heffer, ). We used antibodies specific for GM1–2b and GD1a (belonging to the A‐series of ganglioside biosynthesis, with 1 and 2 sialic acid moieties), and for GD1b and GT1b (from the B‐series, with 2 and 3 sialic acid residues).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6]87,88 In PNS myelin, among all its non-phospholipid metabolome, large amounts of PGs or plasmalogens contribute to its architecture, integrity of adherence of the neuroplasm, and to nerve protection and insulation. [150][151][152][153][154] Further, the neuroplasm interacts with myelin both ways [155][156][157][158][159] , with cadherins [160][161][162][163][164][165][166] and others still to be found [165][166][167][168] as well as to place periaxin 169 with connexin 32 (Cx32). 170 The alignment and points of adherence of the defects can suggest one of the most abundant myelin PGs involved, such as myelin protein zero (P0) which core integral protein replaces the proteolipid protein or PLP found in the CNS myelin.…”
Section: Myelin Aspectsmentioning
confidence: 99%